A survey on problem faced by contractors using design and build contract - Nurhajar, Abd Rahman (2009)
Design and build construction process has been part of the construction industry. Today, the process is growing rapidly in this industry. As it has been grown in popularity, design and build has evolved all manner of hybrids. However, Design and Build also not exclude were faced problem by contractors in the construction industry such as conflicts between contractor and other parties (consultant and owner), Inadequate experience of consultant, problems communication and coordination by contractor with other parties. The aims of the study are to study comparisons between designs & build contract and conventional contract, to identify the common problems and the factors faced by the contractor and to rank the common problems and the factors among contractors. The questionnaires were distributed to the contractor (Class A) registered with Pusat Khidmat Kontraktor (PKK) , grade 7 contractors which registered with construction industry development board CIDB Bumiputera companies and government agencies by hand at Klang Valley. The data from the questionnaire was analyzes in average index and frequency analysis. Result of the survey indicated, five of category problems were identified. There are problem in general aspect, problem in design aspect, problem in financial aspect, problem in quality aspect and problem in time aspect. From the analysis the highest degree of agreement in general aspects is conflicts between contractor and other parties (consultant and owner). It is followed with in quality aspects is change materials order by owner during construction, problem in design aspects is mistakes and discrepancies in design documents, problem in financial aspects is actual price for project higher than owner’s target price and problem in time aspects is delays in commencing work because under-estimated time needed to obtain statutory approvals. Based on the result obtained from questionnaires were identified the problems among contractor are not critical because overall the respondents are agree with that problem. Finally, the information gathered can be used for government sector and contractor to overcome the problem faced by the contractor using design & build contract.